Performance Assessment of an Activated Sludge Wastewater Treatment Plant Treating Chocolate Processing Wastewater - Rizal Aulia Ahadi Putra Karim; Rida Oktorida Khastini; Najmi Firdaus (Tecno Scientifica Publishing, 2026)
The chocolate processing industry generated wastewater containing high concentrations of organic pollutants that could pose significant environmental risks if not properly treated. This study aimed to analyze the characteristics of wastewater generated from the chocolate-based food industry and to evaluate the effectiveness of a Wastewater Treatment Plant (WWTP) employing an activated sludge system. The research was conducted through field observations and laboratory analyses of 33 physical, chemical, and biological parameters at the WWTP inlet and outlet points. Sampling was performed using the grab sampling method in accordance with SNI 6989.59:2008, with a total of 33 samples collected during the period from October 2025 to April 2026. The results indicated that the main pollutant parameters at the WWTP inlet were Biochemical Oxygen Demand (BOD) at 1524 mg/l, Chemical Oxygen Demand (COD) at 6470 mg/l, and Total Coliform at 19,000 MPN/100 ml, all of which exceeded the environmental quality standards. Following the treatment process, the concentrations decreased to 12.94 mg/l for BOD, 54.70 mg/l for COD, and 560 MPN/100 ml for Total Coliform. The removal efficiencies achieved were 99.15% for BOD, 99.15% for COD, and 97.05% for Total Coliform. These findings demonstrated that the combination of chemical treatment and activated sludge processes was effective in reducing organic and microbiological pollutant loads to comply with the environmental quality standards stipulated in the Indonesian Ministry of Environment and Forestry Regulation No. 5 of 2014. Optimal wastewater treatment not only contributed to environmental protection but also supported social responsibility and industrial sustainability.